ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA KELAS XI MIPA 3 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMAN 1 BENAI - Ria Finola Ifanisari; Andrizal Andrizal; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
Critical thinking skills are poured into the K13 to maximize the potential possessed by students. However, in its application in class XI MIPA 3 of SMAN 1 Benai on Islamic Education subjects, it was found that some students did not describe detailed answers when asked questions about learning materials; there are students who answered questions were not in accordance to the directions of the questions; students are more accepting of opinions than arguing; and students tend to be unresponsive when given the opportunity to criticize their friends' statements about learning materials in class. This research aims to determine how the Critical Thinking Skills of class XI MIPA 3 students in Islamic Education subjects at SMAN 1 Benai. This research is a qualitative type with the subjects being students of class XI MIPA 3 at SMAN 1 Benai. Data collection techniques used are interviews, observations, and documentation with data analysis techniques Miles and Huberman model. The results showed that the Critical Thinking Skills of students were generally "good". 16 of 24 indicators of Critical Thinking Skills have been met according to theory. Only one sub-variable is the most problematic, namely "Analyzing Skills" because four of the five indicators have not been met according to theory